2022
DOI: 10.3389/fcell.2022.866857
|View full text |Cite
|
Sign up to set email alerts
|

New Progress in Basic Research of Macrophages in the Pathogenesis and Treatment of Low Back Pain

Abstract: Low back pain (LBP) is quite common in clinical practice, which can lead to long-term bed rest or even disability. It is a worldwide health problem remains to be solved. LBP can be induced or exacerbated by abnormal structure and function of spinal tissue such as intervertebral disc (IVD), dorsal root ganglion (DRG) and muscle; IVD degeneration (IVDD) is considered as the most important among all the pathogenic factors. Inflammation, immune response, mechanical load, and hypoxia etc., can induce LBP by affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 130 publications
1
10
0
Order By: Relevance
“…The findings demonstrated that whereas eosinophils and Th2 cells reduced in the deteriorated nucleus pulposus compared to the normal group, the number of macrophages, CD8T cells, dendritic cells, and Th17 cells rose. The importance of macrophage infiltration in the etiology of IDD has been validated by recent research (Lan et al, 2022;Yan et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…The findings demonstrated that whereas eosinophils and Th2 cells reduced in the deteriorated nucleus pulposus compared to the normal group, the number of macrophages, CD8T cells, dendritic cells, and Th17 cells rose. The importance of macrophage infiltration in the etiology of IDD has been validated by recent research (Lan et al, 2022;Yan et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…This consideration leads to the hypothesis that human IVD cells may not be the sole contributors to the noxious and accelerating inflammatory responses found in degenerating IVD. Moreover, while the role of macrophage-mediated inflammation in IVD degeneration has been well demonstrated [ 32 , 33 , 34 ], little is known about how neuroinflammation, which can be mediated by microglia, is initiated and maintained in LBP.…”
Section: Discussionmentioning
confidence: 99%
“…First, in the probable mechanism of neuroinflammation initiation, diverse inflammatory responses are generally initiated by infiltration of immune cells, such as microglia, through invasive vascular structures. Indeed, most of the currently available studies support a positive correlation between increased innervation of the vascular/neuronal structure, discogenic pain, and inflammatory response [ 25 , 34 , 35 ]. Moreover, several studies have demonstrated that the degenerative IVD microenvironment includes infiltration and phenotypic switching of resident inflammatory-like cells, such as CD11b+, CD 68+, and CD4+ cells [ 2 , 32 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of these proinflammatory factors secreted by cells were found to be markedly elevated in IVDD, which promoted the degradation of extracellular matrix, facilitated the phenotype change of cells and resulted in an imbalance of catabolism and anabolism, thus leading to the occurrence of IVDD. M2 macrophages can secrete anti-inflammatory factors, such as IL-4, IL-1R, IL-10, TGF-β and PDGF, primarily playing anti-inflammatory and promoting tissue repair role [ 37 ]. M1 polarization of macrophages could promote inflammation and damage of NP cells and M2 polarization could be a therapeutic target [ 38 ].…”
Section: Intervertebral Disc Degenerationmentioning
confidence: 99%
“…IVDD is considered as a chronic inflammatory state. The non-surgical treatment only relieves the symptoms, and surgical treatment has the defects of recurrence, aggravation of adjacent segment degeneration and difficulty in restoring normal biological function of the spine [ 37 ]. Research groups have aimed to regulate the redox balance of disc cells as a therapeutic objective to alleviate oxidative stress.…”
Section: Treatments For Ivddmentioning
confidence: 99%